Nicolas and "the script of his power”: on some ethical consequences of the plot twist - Iandoli, Gerardo (E|C, 2020)
“La Paranza dei Bambini” by Roberto Saviano is a novel consisting of three parts, which are in turn divided into chapters. The narrative sequence that will be discussed in the article is placed in a relevant position, since it is found in the last chapter (“Champagne”) of the second part, which has a particularly explicit title: “Fuck and Fuckers”. The goal is to analyze its "communicative power" (Sternberg 1992, p. 100), that is, its ability to produce narrative tension in the reader. In fact, if narrativity, as Meir Sternberg argues, is "the game of suspense, curiosity and surprise between the represented time and the communicated time" (Sternberg 1992, p. 194), then it must be understood that the purpose of each narrative sequence is to arouse a particular emotional reaction in the reader (thymic effect).